Permanent Bilateral Vision Loss in Eclamptic Posterior Reversible Encephalopathy Syndrome. (3rd September 2015) - So, Ki-Youn; Oh, Sun-Young; Yang, Si-Young
Abstract: Posterior reversible encephalopathy syndrome (PRES) classically consists of reversible vasogenic oedema in the posterior circulation territories, which is reversible both clinically and radiologically in the majority of patients after the control of hypertension. The authors describe a 27-year-old eclamptic patient with PRES in accelerated hypertension who revealed permanent vision loss associated with bilateral Purtscher retinopathy. One of the two competing theories that explain vasogenic brain oedema in PRES is excessive autoregulation leading to the dilation of cerebral arterial vessels, particularly in the occipito-parietal vasculatures. Dysfunction of endothelial cells that results in constriction of vessels has also been hypothesised as a cause of PRES. The concurrence of bilateral vaso-occlusive retinopathy and PRES supports the hypothesis that vasoconstriction is a more plausible mechanism of vasogenic oedema in PRES.